Implementation of Role-Playing Learning Models in Biology Lessons of High School Students - Gusmaweti; Meiliza ARDILLA; Wince Hendri (RADINKA JAYA UTAMA PUBLISHER, 2022)
This study aims to look at differences in biology learning outcomes using role playing models and conventional methods (lectures, discussions, question and answer) of class X SMA Negeri Lubuk Linggau. This type of research is experimental research. The population in the study were all students of class X SMA Negeri 1 Lubuk Linggau. Sampling was carried out by purposive sampling technique, then the determination of the experimental class and control class was carried out by random method. Obtained class X.1 as the experimental class, and class X.2 as the control class. The research instrument was used in the form of test questions for cognitive aspects of student learning outcomes, and observation sheets for affective and psychomotor aspects of learning outcomes. Hypothesis testing was carried out by t-test. The results showed that the average score for biology learning outcomes for students using Role Playing was 74.70 and 66.80 with conventional methods. There is a significant difference at the 0.05% alpha level. The results of observations of student learning in the experimental class affective aspects 90.8 and psychomotor and 91.3, while in the control class affective aspects 64.8 and psychomotor 66.6. It can be concluded that the application of the Role Playing method in biology learning is better than conventional learning.